2021
DOI: 10.1186/s12929-021-00772-0
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR and KRAS: a match yet to be made

Abstract: CRISPR (clustered regularly interspaced short palindromic repeats) systems are one of the most fascinating tools of the current era in molecular biotechnology. With the ease that they provide in genome editing, CRISPR systems generate broad opportunities for targeting mutations. Specifically in recent years, disease-causing mutations targeted by the CRISPR systems have been of main research interest; particularly for those diseases where there is no current cure, including cancer. KRAS mutations remain untarge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 168 publications
0
7
0
Order By: Relevance
“…These versatile toolkits have facilitated the management of oncogenic mutations associated with cancer. Three distinct CRISPRdependent approaches have emerged for inhibiting these variants: 1) precisely targeting and disrupting the oncogenic mutation genomes and transcripts using DNAediting and RNA-editing tools, such as the CRISPR/Cas9 and CRISPR/Cas13a 10,13,22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These versatile toolkits have facilitated the management of oncogenic mutations associated with cancer. Three distinct CRISPRdependent approaches have emerged for inhibiting these variants: 1) precisely targeting and disrupting the oncogenic mutation genomes and transcripts using DNAediting and RNA-editing tools, such as the CRISPR/Cas9 and CRISPR/Cas13a 10,13,22 .…”
Section: Discussionmentioning
confidence: 99%
“…CRISPR/Cas technology has witnessed significant advancements in recent years as a powerful gene editing tool for targeted therapies in cancer treatment [10][11][12] . In lung cancer, CRISPR/Cas9 was widely and thoroughly documented as an editing tool to directly target Kras mutations and indirectly inhibit Kras-related molecules, such as KEAP-1, NF1, and EGFR et.al, leading to tumor regression 10 . Additionally, CRISPR/Cas13a has demonstrated the ability to suppress the progression of NSCLC cells by depredating the mutated Kras transcript 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRISPR-Cas-mediated dsDNA breaks often trigger apoptosis and can result in the emergence of inactivating mutations in TP53. Unintentional editing of a genome can lead to profound long-term complications [67][68][69][70]. Pre-existing anti-Cas antibodies in humans may further diminish editing efficiency [71].…”
Section: Clustered Regularly Interspaced Short Palindromic Repeats (C...mentioning
confidence: 99%
“…(64) Studies using CRISPR has been shown to regulate downstream molecules such as PI3K, ERK, Akt, Stat3, and c-myc, and some studies have been conducted using CRISPR to target PI3K in pancreatic cancer. (65) Although CRISPR has been shown a great potential and used to edit genes associated with a variety of diseases, its clinical application in cancer is still in infancy, and there are currently no studies using CRISPR to treat ameloblastoma cases.…”
Section: Clustered Regularly Interspaced Shortmentioning
confidence: 99%